Optimalisasi Peran Sistem Pengendalian Intern dalam Mencegah Terjadinya Penyelewengan Kas dan Aset pada Lembaga Pendidikan Non Pemerintah (Swasta) - Fathiyah Fathiyah (J-MAS (Jurnal Manajemen dan Sains), 2019)
The purpose of this study is to analyze how to optimize the role of internal control system in preventing the occurrence of fraud on cash and assets in non government or private educational institution. Tool of analyzed used in this research is internal control system according to COSO definition and combined with internal control system according to Government Regulation Number 60 Year 2008 with 5 internal control component that is; 1) Control Environment, 2) Risk Assessment, 3) Control Activity, 4) Information and Communication and 5) Monitoring. The result of the research shows that optimizing the role of the internal control system is very helpful to the management in managing the finances and assets owned so as to prevent the occurrence of fraud on the cash and assets in private educational institution. The expectation of the future by optimizing the role of internal control system on cash management and assets in non government/or the private educational institution will be more efficient and effective which will ultimately improve the quality and accountability of the private educational institution.